Managing Herbicide Resistance: Listening to the Perspectives of Practitioners. Procedures for Conducting Listening Sessions and an Evaluation of the Process. (9th August 2018) - Schroeder, Jill; Barrett, Michael; Shaw, David R.; Asmus, Amy B.; Coble, Harold; Ervin, David; Jussaume, Raymond A.; Owen, Micheal D. K.; Burke, Ian; Creech, Cody F.; Culpepper, A. Stanley; Curran, William S.; et al.
Abstract: Seven half-day regional listening sessions were held between December 2016 and April 2017 with groups of diverse stakeholders on the issues and potential solutions for herbicide-resistance management. The objective of the listening sessions was to connect with stakeholders and hear their challenges and recommendations for addressing herbicide resistance. The coordinating team hired Strategic Conservation Solutions, LLC, to facilitate all the sessions. They and the coordinating team used in-person meetings, teleconferences, and email to communicate and coordinate the activities leading up to each regional listening session. The agenda was the same across all sessions and included small-group discussions followed by reporting to the full group for discussion. The planning process was the same across all the sessions, although the selection of venue, time of day, and stakeholder participants differed to accommodate the differences among regions. The listening-session format required a great deal of work and flexibility on the part of the coordinating team and regional coordinators. Overall, the participant evaluations from the sessions were positive, with participants expressing appreciation that they were asked for their thoughts on the subject of herbicide resistance. This paper details the methods and processes used to conduct these regional listening sessions and provides an assessment of the strengths and limitations of those processes.